The effect of service, facility, and security toward tourists’ interest to Adityawarman Museum - Siska Mandalia; Nita Fitria; Taufik Hidayat; Murniarti (International Journal of Applied Sciences in Tourism and Events, 2023)
This study aims to determine the effect of service on tourists' interest in visiting the Adityawarman Museum in West Sumatra, Indonesia. The method used in this research is a quantitative research method. The data collection technique was carried out by filling out a questionnaire. The number of respondents was 100 visitors to the Adityawarman Museum. The data analysis technique used is a validation test, reliability test, classic assumption test, multiple linear regression analysis, determinant coefficient test, and t-test, with all data processed by using SPSS 22. The results showed that service, facilities, and security variables influenced tourists' interest to visit the Museum, while service, facilities, and security variables together influenced tourists' interest to visit. For this reason, this research provides an overview of the Adityawarman Museum manager in maintaining and improving the services, facilities, and tourist safety. Then by providing better services, facilities, and security, it will attract tourists to re-visit the museum so which affects tourist satisfaction. In conclusion, the better the service, facilities, and security at the Adityawarman Museum, the more interest of tourists to visit the Adityawarman Museum will increase.